ax + (a + 1)y = a + 2
We are given that (4, -8) is a solution to this equation.
That means if we substitute 4 in for x and -8 in for y , we will make a true equation.
So the following equation must be true:
a(4) + (a + 1)(-8) = a + 2
We can distribute -8 to the terms in parenthesees and simplify the left side of the equation.
4a - 8a - 8 = a + 2
Add 8 to both sides of the equation.
4a - 8a = a + 2 + 8
Subtract a from both sides of the equation.
4a - 8a - a = 2 + 8
Combine like terms.
-5a = 10
Divide both sides of the equation by -5
a = -2